Y=(-3)(4i)(7i)

Simple and best practice solution for Y=(-3)(4i)(7i) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y=(-3)(4i)(7i) equation:


Simplifying
Y = (-3)(4i)(7i)

Remove parenthesis around (4i)
Y = -3 * 4i(7i)

Remove parenthesis around (7i)
Y = -3 * 4i * 7i

Reorder the terms for easier multiplication:
Y = -3 * 4 * 7i * i

Multiply -3 * 4
Y = -12 * 7i * i

Multiply -12 * 7
Y = -84i * i

Multiply i * i
Y = -84i2

Solving
Y = -84i2

Solving for variable 'Y'.

Move all terms containing Y to the left, all other terms to the right.

Simplifying
Y = -84i2

See similar equations:

| 7x-(4x+3)=1 | | [3y-2]=[26-4y] | | 16y-6=2 | | -x+9-9= | | 121x^2-16=-7 | | T*23=276 | | y=-4.9t^2+26t | | 38+2d=100 | | 82(2)= | | 4x-9.8=4.6 | | n^2+4n-3=9 | | 180-81= | | k^2+14k-54=-3 | | .1(x+1000)-.06=260 | | A=91-2x | | on(x+4)-ln(x+1)=lnx | | 16y+7=19 | | 25x^2-30x+4=0 | | 7+x-9= | | -7x(2x+5)=0 | | 3D+4D+8D-8= | | x^2+18x+35=7 | | 6y+9=11 | | .07x+.12y=690 | | X^2-36=-64 | | -3,33+x=5/3 | | log(x+3)+log(x-3)=2 | | K+33=86 | | -4=x^2+x-6 | | 15t(20t+5)=180 | | 4b(-b-3)-2(b^2-7b-4)= | | -42m-11=103 |

Equations solver categories